The Use of Online Learning Model in Teaching English at SMA Negeri 4 Parepare During Pandemic Covid-19 - Abbas, Ayu Mutmainna; Patahuddin, Patahuddin; Sudarmanto, Sudarmanto (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2023)
Pandemic Covid-19 is a problem that is afflicting almost every country in the world. Learning that is done face-to-face at school has turned into online learning that is accessed at home. This online learning applies to all levels of education, from elementary school to university. All lessons, including English, are conducted online. The change in the system is expected to support learning during pandemics, but it is reaping various problems among the community and even those involved in learning. This research uses qualitative research with the case study method. Participants in this study consisted of seven students and two English teachers at SMA Negeri 4 Parepare. In addition, this study conducted semi-structured interviews to obtain data. The results of this study indicate that the learning carried out during pandemic covid-19 has not been maximally implemented. Teachers and students try to apply the applicable learning system but are hampered by various problems such as internet network access and difficulty understanding the material.